A Few Problems Elucidated . And New Questions Raised by Recent Dorset Finds in the North Baffin Island Region - Mary-Rousselière, O.M.I., G. (ARCTIC, 1979)
Several recent discoveries, made possible by exceptional conditions of preservation at the Nunguvik site (North Baffin Island), provide new information, among others, on the kayak and sled of the Dorset culture, and suggest that the Dorset people used skis. An engraved bone plate from the Dorset site of Sannirajaq (Hall Beach) pictures, associated with a caribou, an enigmatic object variously interpreted as a sled, a trap for caribou, or a wicker-trap.